A Radiography of English Elements in Romania - Pungă Loredana (Romanian Journal of English Studies, 2018)
This article aims to offer some insight into manifestations of language contact in the particular case of English and Romanian. It focuses on lexical, morpho-syntactic, semantic and discourse-related aspects of the influence of the former in the context of the latter. In particular, after pointing out the areas in which anglicization is especially obvious, attention is paid to: the adaptation of anglicisms so as to fit Romanian syntactic patterns; code switching and its functions; borrowing-triggered semantic change; lexical-semantic calques; and patterns of English written genres imposing new standards for equivalent Romanian genres.